Translation as a Vocabulary Teaching Aid in ESP - Olivia CHIROBOCEA-TUDOR (Scientific Bulletin of the Politehnica University of Timişoara: Transactions on Modern Languages, 2021)
This article represents a part of the more extensive research started in 2018 from the premise that translation activities are in fact very useful in ESP classes when used as language learning technique, as argued with evidence, and continues the previous series of articles that studied this topic. This installment deals with the benefits translation activities have on vocabulary acquisition in ESP when properly implemented in the classroom. The conclusions are based on empirical observations and on the previous research which included a case study regarding learners’ attitudes towards this type of activity.